Ethanol production from cassava starch by protoplast fusants of Wickerhamomyces anomalus and Galactomyces candidum. Issue 1 (1st January 2020) - Adeleye, Tolulope Modupe; Kareem, Sharafadeen Olateju; Bankole, Mobolaji O.; Atanda, Olusegun; Adeogun, Abideen I.
ABSTRACT: The potential of protoplast fusants of Wickerhamomyces anomalus and Galactomyces candidum isolates for ethanol production from cassava starch was evaluated. The protoplasts were obtained from 18 h yeast cells digested by zymolase and fused by polyethylene glycol (PEG). Regenerated recombinants were randomly selected and examined for desired marker traits: rate of fermentation of glucose, maltose and ethanol tolerance. Cassava starch hydrolysates were obtained by the amylolytic action of partially purified amylase extracts from Aspergillus species . Three of the selected fusants exhibited improvements in fermentation parameters over the parents. Enhanced ethanol tolerance of (25% v/v) as against 20% of the parents was exhibited by fusants R4 and R7. All isolates displayed higher ethanol productivity than CO2 . The highest values of carbon dioxide productivity (4.79 L/L.h), volumetric ethanol productivity (11.54 g/L.h) and an ethanol mass concentration of 110.88 g/l were obtained from the fermentation by R1. Fusant R1 also had the highest fermentation efficiency (80%) and actual ethanol recovery (10.19%), as compared to other fusants and the parent yeast isolates. Parent isolates and selected fusants were characterized using molecular tools. The possibility of the occurrence of a genetic recombination in selected fusants as a result of protoplast fusion was observed.